MANAJEMEN LEMBAGA PENDIDIKAN ISLAM BERBASIS MASYARAKAT DAN SEKOLAH - Sodiah Sodiah (Sosial Budaya, 2016)
The institutional Islamic education progress need an open system from superior to subordinate. The longer bureaucracy has to be passed in an education implementation cause the smaller effectiveness and efficiency achievement. Therefore in improving institutional Islamic education management is applied society based management and school based management. The society based management gives large chance for learning community also its general to form Islamic education purpose and education policy that multi-benefit. Thus school based management as a result from the autonomy law so that managers have authority to manage sources and human resources for achieving the objective of institutional Islamic education.